2011
DOI: 10.2174/138920011797470128
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Ginseng and its Interactions with Drugs

Abstract: Ginseng is an herbal medicine used worldwide. It is reported to have a wide range of pharmacological activities because of a diversified group of steroidal saponins called ginsenosides. Compared to extensive pharmacological studies of ginseng, the pharmacokinetics, especially the metabolism of this herb, has received less attention. In this article we review the known pharmacokinetic data on ginseng. Understanding ginseng’s pharmacokinetics may reduce the potential for interactions in patients who use both gin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 57 publications
2
69
0
Order By: Relevance
“…There are also many reports that ginseng has antiaging and antioxidant properties (8). The various pharmacological and biological effects of ginseng are mainly mediated by compounds from the saponin group, called ginsenosides (9). Accumulating evidence has revealed that the major functional components of ginsenoside have antiinflammatory, antidiabetic and antitumor effects (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…There are also many reports that ginseng has antiaging and antioxidant properties (8). The various pharmacological and biological effects of ginseng are mainly mediated by compounds from the saponin group, called ginsenosides (9). Accumulating evidence has revealed that the major functional components of ginsenoside have antiinflammatory, antidiabetic and antitumor effects (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous reviews on ginseng-drug interaction have been already published [47, 48], no article has critically reviewed ginseng-anticancer drug combination for improvement of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Its bioavailability is low. Gut microbial flora is responsible for the production of different metabolites such as ginsenosides, polysaccharides, peptides, and gintonins [22,23] . However, because of poor membrane permeability and low solubility, absorption of these products is limited.…”
Section: Discussionmentioning
confidence: 99%